Benefit or Coercion: the Perception of Compulsory Service Programs by Doctors Who Are Employed on the Periphery - Ekaterina Aleksandrovna Sharepina; Aleksandra Konstantinovna Lomanova (Интеракция. Интервью. Интерпретация)
This article examines the typology of evidence perception among veterinarians specializing in small domestic animals in Russia. Based on the analysis of 35 interviews, three main types of evidence perception by SDA veterinarians are identified: traditional, phonetical, and resident. The article also analyzes how these types influence the professional practices of veterinary specialists and considers them in the context of evidence-based medicine and its current development. The targeted recruitment program is one of the key initiatives to address the shortage of medical personnel. In recent years, the proportion of targeted placements within the budgetary intake has increased, and measures to ensure the return of targeted recruits to work in their designated areas have been intensified. However, the results of the program's implementation remain controversial. Similar foreign programs are classified either as financial incentives for doctors to work in remote areas or as coercive measures. Research indicates that perceiving the program solely as a coercive measure creates a negative attitude towards it and reduces the proportion of those who complete their service. This article, based on 21 biographical interviews, examines the perceptions of the targeted recruitment program among doctors who completed their residency and internship under the program and are now working in peripheral municipalities of the Central Federal District. The study results show that the evaluation of the program by the participating doctors is broader than the dichotomy of financial benefits from receiving free education and coercion associated with the obligation to work off the service. Implicit costs and benefits were identified, and their balance determines the perception of the targeted recruitment program at different stages: admission, education, and return for service. The negative view of the program is linked to a lack of understanding among targeted recruits of the financial benefits of participation, the necessity of relocating from the place of medical education, reluctance to sever social ties formed over the years of study, lack of conditions for primary professional socialization, uncomfortable working and living conditions after returning to serve. For some informants, the forced nature of the service is offset by opportunities for obtaining prestigious education, prospects for gaining real work experience, professional and career growth, additional financial and housing support, support from colleagues and administration, as well as personal and family factors related to returning to their hometown or personal demographic events.